Sn(ii) induced concentration dependent dynamic to static excimer conversion of a conjugated naphthalene derivative1. Issue 32 (28th August 2015) - Adhikari, Susanta; Mandal, Sandip; Ghosh, Avijit; Guria, Subhajit; Das, Debasis
<x xml:space="preserve">Abstract</x> The colorimetric and fluorescence recognition of Sn2+ has been achieved using a naphthalene appended diformyl-p-cresol derivative (L). The dynamic excimer, observed up to 50 μM Sn2+, gradually converts to a static type above 50 μM Sn2+. DFT calculations support the experimental findings.